Jurisdiction by Subject Matter of the Labor Courts of Peace - Flores Alanoca, Jael Ángel (2024)
The administration of justice by the Judicial Branch begins with the Magistrates' Courts, which constitute the first level within the hierarchical organization of this branch of government. They are followed, in ascending order, by the Specialized Courts, Superior Chambers and Supreme Chambers, which assume a series of competencies assigned to them by the national legal system. In this article we will address the competence by subject matter of the Labor Magistrates Courts, with emphasis on the expansion of their competencies, reviewing the changes produced in the 02 Labor Procedural Laws of Peru and the introduction of competencies made by the IX Supreme Labor Plenary of the year 2022.Although the Law is an important normative instrument in national law, nowadays jurisprudence has gained great importance within the sources of law, assuming a creative role, thus overcoming the traditional role of mere applicator and interpreter of the Law. This is the case of the jurisprudence of the Supreme Court of the Republic and the Constitutional Court, which have contributed to the legal development of the country with a wide margin of legitimacy when they establish criteria nurtured with a high content of justice that society expects. In the case of the competence of the labor courts of peace, in this article we notice an absence of concern on the part of the Legislative Power in facing the problem presented; assumed in part by the Supreme Court of the Republic through a Supreme Labor Plenary. We will see if the legal solution given is complete or if it requires additional measures.